Efforts to Improve Grade 12 Students’ Learning Outcomes on the Topic of Electrolysis Through the Problem-Based Learning Model - Suci Puji Setyowati (Scientia Publica Media, 2026)
This study investigates the implementation of Problem-Based Learning (PBL) to improve the chemistry learning outcomes of 12th-grade students on the topic of electrolysis. Chemistry learning often presents difficulties because many concepts are abstract, especially those involving microscopic processes such as ion movement and redox reactions. Preliminary observations revealed that more than 40% of students in class XII MIPA-1 at SMA Kolese De Britto had not yet reached the Minimum Completion Criteria (KKM = 80) on the topic of electrochemistry, with an average score of 70.57. To address this issue, PBL was applied as it emphasizes contextual problem-solving, student engagement, and the development of 21st-century skills. This research used a Classroom Action Research (CAR) design conducted in two cycles, each including planning, implementation, observation, and reflection. The participants were 30 male students aged 17–18. The instruments consisted of: (1) a learning achievement test with 10 essay items developed according to basic competencies and scored with a rubric, (2) an observation sheet with 10 indicators of participation, collaboration, and discipline, (3) a Likert-scale questionnaire with 20 statements to assess motivation, perception, and problem-solving skills, and (4) documentation of learning activities through photos, field notes, and student products. Data were analyzed both quantitatively (mean scores, mastery percentages) and qualitatively (observations, questionnaires, reflections). The results showed a significant increase in student achievement. The average score rose from 70.57 (33.33% mastery) in the pretest to 79.57 (63.33% mastery) after Cycle I, and 85.16 (80% mastery) after Cycle II. Questionnaire results also indicated improved motivation and collaboration, from 85.07% in Cycle I to 89.59% in Cycle II. Observations confirmed more balanced participation and greater problem-solving engagement. Overall, this study concludes that PBL is effective for improving understanding of electrolysis while fostering critical thinking, collaboration, communication, and creativity. The findings highlight that contextual problem-solving and guided discussions are crucial for bridging abstract chemistry concepts with real-world applications, making PBL a powerful approach for chemistry education.